The South African Gen Z Short-Term Insurance Paradox: Exploring Digital Journeys towards Brand Engagement and Trust - Mkele, Loyiso (The IIE, 2025)
The South African short-term insurance (STI) sector faces a paradox: although Generation Z (Gen Z) is digitally native and fluent in mobile and online platforms, it remains largely disengaged from insurance services. Despite insurers’ significant digital investments, Gen Z’s interactions with STI brands are limited by perceived complexity, a lack of transparency, and low trust, particularly in South Africa’s unequal socio-economic landscape. This study investigates how digital customer journeys shape Gen Z’s perceptions and engagement with STI brands, addressing the tension between their addressing the tension between their digital fluency and reluctance to engage. Anchored in an interpretivist paradigm, the study applies Social Exchange Theory (SET) to explain how trust develops through perceived reciprocal value in brand interactions, and Generational Cohort Theory (GCT) to contextualise how shared generational experiences shape Gen Z’s digital expectations and engagement behaviours. Using a qualitative design, the study conducted 12 semi-structured interviews with South African Gen Z participants and analysed them using thematic analysis. The findings revealed seven key themes: perceived value, digital friction, transparency, peer influence, brand relatability, data privacy concerns, and financial literacy gaps. These findings demonstrate that trust is constructed through transparent, responsive, and value-driven exchanges, and eroded by perceived opacity, complexity, and aligned communication. The study contributes to generational marketing and digital engagement literature by situating Gen Z’s insurance hesitancy within a socio-digital paradox characteristic of emerging markets. Practically, it provides actionable insights for STI brands to redesign digital touchpoints, balancing automation with human reassurance, transparency, and education to foster meaningful engagement and long-term trust.
Keywords: Generation Z; LAW/JURISPRUDENCE::Private law::Insurance law; Digital customer journey; Brand trust; Brand engagement